Efektivitas Pembelajaran Kooperatif Tipe Talking Chips untuk Meningkatkan Keterampilan Komunikasi Ilmiah Peserta Didik pada Materi Sistem Ekskresi - Saniah, Saniah; Ratna Yulinda; Maya Istyadji (CV.ITTC INDONESIA, 2025)
This research investigates how effective the Talking Chips type of cooperative learning model is in enhancing students' ability to communicate scientifically, particularly in the excretory system topic. A quasi-experimental design with a Nonequivalent Control Group format was employed. The control group received instruction through traditional teaching methods, whereas the experimental group implemented the Talking Chips strategy. The study involved 60 eighth-grade students from SMP Negeri 13 Banjarmasin as participants. Research tools included observation forms, surveys, and both pretests and posttests. The data were examined using qualitative descriptive analysis along with the Independent Sample T-Test. The results showed: (1) the experimental group achieved a scientific communication score of 61.15 (moderate level), while the control group scored only 47.09 (low level); (2) a significant difference in scientific communication skills existed between the two groups; and (3) learning outcomes also differed significantly between them. The N-Gain score for the control group was 0.55, indicating moderate improvement, while the experimental group reached 0.77, classified as a high level of improvement. These findings suggest that applying the Talking Chips cooperative learning model effectively enhances students’ scientific communication skills when learning about the excretory system.